2021
DOI: 10.1109/access.2021.3071766
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Deep Random Neural Network for Cyberattack Detection in the Industrial Internet of Things

Abstract: The Industrial Internet of Things (IIoT) refers to the use of traditional Internet of Things (IoT) concepts in industrial sectors and applications. IIoT has several applications in smart homes, smart cities, smart grids, connected cars, and supply chain management. However, these systems are being more frequently targeted by cybercriminals. Deep learning and big data analytics have great potential in designing and developing robust security mechanisms for IIoT networks. In this paper, a novel hybrid deep rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 24 publications
0
55
0
Order By: Relevance
“…Firms showed benefits, such as an increase of productivity, and faster time responses to suppliers and consumers. RA from the Adoption of decision-making processes is more relevant for organizations in logistics, maritime (Mileski et al, 2018) and manufacturing organizations (Huma et al, 2021;Khaw et al, 2021) than for those organizations in the service industry. On a comparative note, Yeboah-Ofori et al (2021), highlighted the following sectors as cyber vulnerable: Energy, Communication, Transport, Health-care and Manufacturing, and calls on cybersecurity to include the global delivery of physical goods plus the delivery of software.…”
Section: Discussionmentioning
confidence: 99%
“…Firms showed benefits, such as an increase of productivity, and faster time responses to suppliers and consumers. RA from the Adoption of decision-making processes is more relevant for organizations in logistics, maritime (Mileski et al, 2018) and manufacturing organizations (Huma et al, 2021;Khaw et al, 2021) than for those organizations in the service industry. On a comparative note, Yeboah-Ofori et al (2021), highlighted the following sectors as cyber vulnerable: Energy, Communication, Transport, Health-care and Manufacturing, and calls on cybersecurity to include the global delivery of physical goods plus the delivery of software.…”
Section: Discussionmentioning
confidence: 99%
“…Refs. [21,22], authors found that the conventional Internet of Things (IoT) technology is used in the industrial sector. The extensive expansion of IoT in the industrial sector gives rise to the obstruction of information security.…”
Section: Related Workmentioning
confidence: 99%
“…Smart industrial frameworks require multiple synchronized processes that require lower latency and higher reliability to obtain the desired performance [164,165]. Furthermore, the DL techniques used in IIoT should be capable of dealing with these challenges as well as other aspects such as resource management and network deployment [166].…”
Section: Low Latency and Improved Reliabilitymentioning
confidence: 99%